How Different Drivers of Liability of Foreignness Affect Emnes Asymmetrically at the Pre-M&A Stage: Static and Dynamic Views - Zhu, Hua; Qu, Yi (Asian Development Policy Review, 2022)
This study investigates how the drivers of liability of foreignness (LOF) influence the likelihood of emerging multi-national companies completing overseas acquisition deals and explores contingencies that moderate the adverse effects of LOF from both static and dynamic perspectives. We test our hypotheses and find that (1) statically, the formal institutions of laws and regulations per se as well as culture distance are sources of LOF, rather the distance between the laws and regulations of home and host countries. (2) Organization-inherent characteristics, like an industry that may trigger legitimacy concerns, have moderating effects on LOF, while state-ownership is not proved to be a significant moderating factor. (3) Dynamically, different drivers of LOF exert asymmetric effects on firms with prior international experience: cultural distance ceases to exert a significantly negative influence on the completion of acquisitions, but the negative effect stemming from formal institutions is reinforced.